(untitled) (Res Gesta, 2020)
For four days in October, 1934, The 32nd International Eucharistic Congress was celebrated and organized in honor of Jesus in the Bless Sacrament. For the first time, the South American continent was distinguished to hold the religious encounter, choosing Buenos Aires as venue. This was considered an honor by the local Catholic Church. The Congress caused an eucharistic fever and it demonstrated the popular Christian fervour of the Argentinian society, after decades of secularist progress from the State and the civil institutions. The event revealed the popular catholic mass pressure to occupy increasingly prominent spaces in the public and social life, fact manifested in the massive support for each Congress act throughout the country. The magnitude of the Congress was reflected by the graphic media, which increasingly widened their field of penetration towards the different professional sectors. Among the long-standing massive publications in the 30s of the 20th century, the weekly women´s magazine Para Ti, by Editorial Atlántida, represented a sample of the women´s readings of the rising middle and popular urban areas. From its sections dedicated to topical issues, the magazine covers the development of the Eucharistic Congress and it reveals the role of women in the religious manifestation.